Nitrogen fertilization split in green corn under rainfed system - Facundo Aragão, Márcio; Tavares, Ronier; Nascimento dos Santos, Maria de Fátima; Silva Lima, Joilson; Pinheiro Neto, Luis Gonzaga (Revista Ceres, 2023)
The objective of this work was evaluating the nitrogen fertilization splitting on the performance of green corn, grown in rainfed system. The experiment was carried out in Forquilha, Ceará state. Two varieties of corn (Sweet and Gorutuba) were used in the experiment, grown in five types of nitrogen fertilization in the crop cycle (one; three; six; nine; and twelve applications). The variables evaluated were: plant height, stem diameter, number of leaves of the plant, plant fresh mass, plant dry mass, ear mass plant-1, marketable ear mass plant-1, marketable husked ear mass plant-1, marketable unhusked ear mass plant-1, number of ear plant-1, number of marketable ear plant-1, length of husked marketable ear, length of marketable unhusked ear, diameter of marketable husked ear, diameter of marketable unhooked ear, number of rows marketable ear-1 and number of grains row-1 of marketable ear. The data were subjected to analysis of variance by the F test (P < 0.05) and the treatment means were compared by the test of Tukey (P < 0.05) and subjected to regression analysis. It was observed that the split of nitrogen fertilization promoted the development of the two varieties of corn studied. It was found that the split, performed in six applications, provided greater vegetative and reproductive development of the corn varieties.